2017
DOI: 10.1093/femsre/fux001
|View full text |Cite
|
Sign up to set email alerts
|

Formation, physiology, ecology, evolution and clinical importance of bacterial persisters

Abstract: Persisters are transiently tolerant variants that allow populations to avoid eradication by antibiotic treatment. Their antibiotic tolerance is non-genetic, not inheritable and results from a phenotypic switch from the normal, sensitive cell type to the tolerant, persister state. Here we give a comprehensive overview on bacterial persistence. We first define persistence, summarize the various aspects of persister physiology and show their heterogeneous nature. We then focus on the role of key cellular processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
272
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(316 citation statements)
references
References 372 publications
(763 reference statements)
3
272
0
6
Order By: Relevance
“…We suggest then that the terms VBNC and persistence describe the same phenotype for dormant cells and that the term VBNC should be replaced with persister cells since VBNC cells do not represent a separate cell phenotype. In addition, since persister cells have been found in nearly all strains that have been tested (Van den Bergh et al ., ), and we have shown that VBNC cells are persister cells in E. coli , our results suggest that what have been characterized previously as VBNC cells for non‐laboratory strains should be persister cells as well. Corroborating this expectation, we found the natural isolate E. coli O157:H7 also formed persister cells under VBNC‐inducing conditions (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 80%
“…We suggest then that the terms VBNC and persistence describe the same phenotype for dormant cells and that the term VBNC should be replaced with persister cells since VBNC cells do not represent a separate cell phenotype. In addition, since persister cells have been found in nearly all strains that have been tested (Van den Bergh et al ., ), and we have shown that VBNC cells are persister cells in E. coli , our results suggest that what have been characterized previously as VBNC cells for non‐laboratory strains should be persister cells as well. Corroborating this expectation, we found the natural isolate E. coli O157:H7 also formed persister cells under VBNC‐inducing conditions (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The ability of SPI009 to directly kill persister cells, combined with its excellent activity in combination with distinct classes of antibiotics, suggests that SPI009 belongs to the first class. Several compounds capable of directly killing persister cells have been described and use different strategies to kill persister cells, such as depolarization and destruction of the cell membrane, DNA cross-linking, inhibition of essential enzymes, and generation of reactive oxygen species (20,51,52). Additional research will be necessary to further unravel the mode of action, but preliminary data suggest that SPI009 acts primarily by causing membrane damage (V. Defraine et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The targeting of persisters is therefore likely to greatly improve outcomes for patients with chronic infectious diseases. Despite the clear clinical relevance of persisters, few antipersister compounds have been described in the literature (20). Contributing to this is the still limited knowledge of the mechanisms behind persister formation in P. aeruginosa, the fact that multiple, redundant pathways seem to be involved, and the observation that the processes implicated in persistence seem to be species specific (21,22).…”
mentioning
confidence: 99%
“…The EMBO Journal 38: e101876 | 2019 ª 2019 The Authors which was however reported in replicating cells too (Dhar et al, 2016;Van den Bergh et al, 2017). Fluoroquinolones are a case in point of how complex drug persistence can be.…”
Section: Of 19mentioning
confidence: 99%